Delivery Information About Global Warming With Internet Media Using PHP And MySQL - Abdul Rahman; Fitri Sjafrina, SKom, MM (Jurnal Sistem Informasi, 2007)
Global warming is a view of the future that will happen in the future if people are not well aware about the importance of protecting the environment. The author proposes that by creating a website about global warming, which is intended to provide information about environmental issues and global warming in particular that occurred in Jakarta. Such information that is only in the authors limit the scope of the city which will be presented in the form of websites that contain menus which are interrelated.Definition of global warming is increasing the average temperature of the earth's surface due to increasing emissions of greenhouse gases in the atmosphere. Global warming and climate change that occurred in Indonesia at this time due to human activities, primarily related to the use of fossil fuels (petroleum and coal) and other activities related to forests, agriculture, and livestock.The author proposes a website that provides information about the environment, especially global warming, which is intended to provide information about environmental issues and global warming in particular that happened in Jakarta, because in the website there is news that can provide useful information for visitors , in addition the website also provides a forum for visitors to the website to submit an article or opinion about global warming on-line.In order for the information contained in this website is becoming more widely expect the author comments, articles or news from our website visitors that can be sent directly through this website.